2018
DOI: 10.2215/cjn.03990318
|View full text |Cite
|
Sign up to set email alerts
|

CKD in Patients with Bilateral Oophorectomy

Abstract: This article contains a podcast at https://www.asn-online.org/media/podcast/CJASN/2018_10_11_CJASNPodcast_18_1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 46 publications
(53 reference statements)
1
17
0
Order By: Relevance
“…Utilizing a novel approach to address the issue of sex and CKD progression, Kattah et al 48 matched 1653 women who underwent bilateral oophorectomy before age 50 years with women whose ovaries were intact and found that the incidence of CKD, over a median follow-up of 14 years, was greater in those with surgical menopause (adjusted hazard ratio, 1.42). The risk of CKD was also related to whether the women received estrogen therapy and to the duration of such therapy.…”
Section: Sexual Dimorphism In the Progres-sion Of Chronic Kidney Diseasementioning
confidence: 99%
“…Utilizing a novel approach to address the issue of sex and CKD progression, Kattah et al 48 matched 1653 women who underwent bilateral oophorectomy before age 50 years with women whose ovaries were intact and found that the incidence of CKD, over a median follow-up of 14 years, was greater in those with surgical menopause (adjusted hazard ratio, 1.42). The risk of CKD was also related to whether the women received estrogen therapy and to the duration of such therapy.…”
Section: Sexual Dimorphism In the Progres-sion Of Chronic Kidney Diseasementioning
confidence: 99%
“…This process is presumed to have led to the emergence of a number of complications, such as hot flashes (or vasomotor symptoms), chronic kidney disease (CKD), cardiovascular disease, and neurodegenerative disease ( Schindler et al, 2009 ; Torres et al, 2017 ) ( Williamson et al, 2019 ). Of those conditions, a common comorbidity in women with menopause is closely linked to the process of CKD development, which increases mortality ( Kattah et al, 2018 ; Vellanki and Hou, 2018 ). Although endogenous estrogen plays a critical role in the protection of renal function, the initiation of hormone replacement therapy (HRT) is recommended to stop or reverse this decline.…”
Section: Introductionmentioning
confidence: 99%
“…A recent cohort study of women who underwent bilateral oophorectomy before the onset of menopause revealed that the risk for incident CKD was higher vs in an agematched group that did not undergo oophorectomy, suggesting that the premature depletion of endogenous estrogen due to surgical procedures could accelerate the deterioration in kidney function. 26 However, observational studies evaluating the effect of Odds ratio…”
Section: Discussionmentioning
confidence: 99%